Advanced glycation end products in food and their effects on intestinal tract. Issue 11 (17th June 2022) - Nie, Chenzhipeng; Li, Yan; Qian, Haifeng; Ying, Hao; Wang, Li
Abstract: With the development of living standards, harmful substances in diet and food safety have seriously endangered people health and life. Advanced glycation end products (AGEs), which formed by Maillard reactions in processed food, have been shown a significantly associated with many chronic diseases, such as nephropathy, atherosclerosis, Alzheimer's disease, and tumors. In recent years, the research about diet advanced glycation end products (dAGEs) have widespread controversy in academia. The main arguments include the production mechanism of dAGEs, metabolic pathways, and relationships with chronic diseases, especially related to the intestines, gut microbiota, and intestinal disorders. So this review attempts to briefly summarize the dAGE in following aspects, including the influencing factors, metabolism, absorption, and so forth. In addition, the effects of dAGEs on intestinal health and gut microbes were discussed, which can offer a goal for boff in to design low dAGEs products and provided some perspectives for further study with AGEs in the future.